Analyzing Teachers' Use of Metadiscourse: The Missing Element in Classroom Discourse Analysis - Tang, Kok-Sing (John Wiley & Sons, 2017)
Metadiscourse, or metatalk, is a discursive resource used in virtually any text or conversation to organize its content or signal the author's stance toward the content. Despite its prevalence in classroom talk, few have examined the role of metadiscourse and how it assists teachers and students to manage classroom communication of scientific knowledge. Thus, the purpose of this study is to analyze how science teachers use metadiscourse to construct scientific knowledge with their students. Based on a corpus of classroom video data, I developed a typology of metadiscourse commonly found in science classroom discourse. The typology comprises six major categories of metadiscourse, namely text connective, knowledge connective, activity connective, attitude marker, epistemology marker, and interpretive marker. In addition, I showed how the analysis on metadiscourse was necessary to complement the gaps from classroom analysis focusing on the interaction and content development aspects of classroom talk, particularly during the opening and reviewing stages of constructing a scientific explanation. With a better understanding of metadiscourse, its potential use as a pedagogical intervention to promote science learning is then discussed.